Flipped Classroom with Inquiry-Based Learning (5E) Enriching Science Games on Science Learning Achievement, Problem Solving Abilities, and Satisfaction in Learning Management of Sixth Grade Students - Soimaneewan, Thiwaporn; Chaiprasert, Pattaraporn; Thongsorn, Parinya (Journal of Buddhist Education and Research (JBER), 2025)
The purpose of this research was to: 1) study science learning achievement and problem-solving abilities before and after learning management using flipped classroom with inquiry-based learning (5E) enriched with science games; 2) study science learning achievement after learning management against the 70 percent criterion; 3) study satisfaction with the learning management. The participants were 32 sixth-grade students at Watsadet School in the first semester of the 2024 academic year. The research instruments consisted of: 1) a lesson plan using flipped classroom with inquiry-based learning (5E) enriched with science games; 2) a learning achievement test; 3) a problem-solving abilities test; and 4) a student satisfaction questionnaire. The data were analyzed using mean and standard deviation. The results of this research indicated that: 1) the post-test scores of learning achievement using flipped classroom with inquiry-based learning (5E) enriched with science games were higher than the pre-test; 2) the post-test scores of learning achievement after learning management were higher than the 70% criterion; 3) the post-test scores of problem-solving abilities were higher than the pre-test; 4) student satisfaction with flipped classroom with inquiry-based learning (5E) enriched with science games was at a high level.